1976
DOI: 10.1083/jcb.69.3.721
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and molecular characteristics of crayfish photoreceptor membranes.

Abstract: The ultrastructure of photoreceptor cells of the crayfish (P. clarkii) has been examined by means of thin sections and freeze-fracturing. The study reveals that in the photoreceptor membranes there are particles associated primarily with the A faces of freeze-fracture preparations which have a mean diameter of 80-84 A and a density of 6,600 per per micrometer2. Treatment of the retina with digitonin (a substance capable of extracting visual photopigments) in Ringer's causes marked disruption of the hexagonal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1977
1977
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 32 publications
1
11
1
Order By: Relevance
“…Freeze fracture studies and also absorption measurements in other invertebrate photoreceptors suggest that the pigment molecules are packed in the membrane I3-2 at a density of 3000-20,000 am-2. Fernandez & Nickel (1976) made an estimate based on both methods in crayfish and Muri, Coles & Baumann (1976) did the same for the honeybee: the mean of their results is about 4000 /sm-2. If this figure is assumed for Limulu8 ventral photoreceptor then the membrane area is calculated to be 6*7 x 105 ,um2.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Freeze fracture studies and also absorption measurements in other invertebrate photoreceptors suggest that the pigment molecules are packed in the membrane I3-2 at a density of 3000-20,000 am-2. Fernandez & Nickel (1976) made an estimate based on both methods in crayfish and Muri, Coles & Baumann (1976) did the same for the honeybee: the mean of their results is about 4000 /sm-2. If this figure is assumed for Limulu8 ventral photoreceptor then the membrane area is calculated to be 6*7 x 105 ,um2.…”
Section: Discussionmentioning
confidence: 97%
“…Freeze fracture studies and also absorption measurements in other invertebrate photoreceptors suggest that the pigment molecules are packed in the membrane I3-2 at a density of 3000-20,000 am-2. Fernandez & Nickel (1976) made an estimate based on both methods in crayfish and Muri, Coles & Baumann (1976) (Fioravanti & Fuortes, 1972). Because of this striking contrast, and because of the scatter of our results (particularly the ratio of C measured in the dark and in the light) it was desirable that the conclusion should be confirmed by other methods: this has been done by Brown et al (1979) Spread of excitation from a photoisomerized rhodopsin molecule It has been shown that in the photoreceptor of the leech the light-induced increase in membrane conductance occurs on, or close to, the microvilli (Fioravanti & Fuortes, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…One type, the R lobe, contains all the rhabdom. Several types of evidence in other systems, including microspectrophotometry (Langer and Thorell, 1966), freeze-fracture (Nickel and Menzel, 1976;Fernandez and Nickel, 1976;Eguchi and Waterman, 1976), and electrophysiology of the developing eye (Eguchi et al, 1962) indicate that the rhabdom contains the photosensitive pigment in invertebrates. The R lobe also contains the organelles, which are shown in the lateral eye (Chamberlain and Barlow, 1979) to be part of the rhabdom breakdown process.…”
Section: Segmentation Of Ventral Photoreceptorsmentioning
confidence: 99%
“…In all cases in which both the rhabdomeric particle density and rhodopsin content were studied, the mutations or vitamin A deprivation was found to reduce both these quantities, supporting the idea that at least the majority of the rhabdomeric membrane particles are closely associated with rhodopsin. Vitamin A deprivation and the mutations also reduced the number of particles in the plasma membrane as in the rhabdomeric membrane, suggesting that both classes of membrane contain rhodopsin .Freeze-fracture studies of the photoreceptors have shown that there are numerous membrane particles on the fracture face of both the outer segment disk membrane of vertebrate photoreceptors (36, 37, and references cited therein) and the rhabdomeric microvillar membrane of invertebrate photoreceptors (3,5,8,9,14,22,26,32) . Several lines of evidence suggest that these membrane particles are correlated with the presence of rhodopsin.…”
mentioning
confidence: 99%